2015
DOI: 10.1002/pbc.25439
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic donor availability for hematopoietic stem cell transplantation in children with sickle cell disease

Abstract: Hematopoietic stem cell transplant is curative of sickle cell disease (SCD) but limited by donor availability. Searches for 85 patients with SCD without matched sibling donors from 2009-2013 using modern techniques (allele-level HLA matching for unrelated donors and higher total nucleated cell doses for umbilical cord blood (UCB)) showed potential match probabilities of 20% for 8/8 HLA-matched unrelated donors, 84% for 7/8 donors, and 97% for two 4-6/6 UCBs suitable for ex-vivo expanded/double cord transplant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…However, the cumulative incidence of chronic graft-versus-host disease (GVHD) was high at 62%, including 6 patients who died from the complication, making these results less encouraging. While investigators will undoubtedly work toward decreasing this GVHD risk a major obstacle that remains is the probability of finding an HLA-matched unrelated donor who actually proceed with donation for SCD transplant is as low as 9% [32]. This likely reflects a larger issue of insufficient donors of African descent represented on donor registries given that the vast majority of patients with SCD are of African descent.…”
Section: Current State Of Hematopoietic Stem Cell Transplantation Formentioning
confidence: 99%
See 1 more Smart Citation
“…However, the cumulative incidence of chronic graft-versus-host disease (GVHD) was high at 62%, including 6 patients who died from the complication, making these results less encouraging. While investigators will undoubtedly work toward decreasing this GVHD risk a major obstacle that remains is the probability of finding an HLA-matched unrelated donor who actually proceed with donation for SCD transplant is as low as 9% [32]. This likely reflects a larger issue of insufficient donors of African descent represented on donor registries given that the vast majority of patients with SCD are of African descent.…”
Section: Current State Of Hematopoietic Stem Cell Transplantation Formentioning
confidence: 99%
“…Unrelated donor transplant for SCD is still in early stages, but even when including fully matched unrelated donors and suitable single cord blood units as graft sources, over half of the patients may still not have a suitable donor option [32]. Haploidentical, or HLA half-matched, donors have also been considered as a graft source since the majority of patients should have a first degree relative who could be a potential donor.…”
Section: Current State Of Hematopoietic Stem Cell Transplantation Formentioning
confidence: 99%
“…A recent study with detailed matching demonstrated that the chances of finding a potential allelic 8/8 HLA-A,-B,-C and -DRB1 MUD was only 19%. 28 Combining 5/6 and 6/6 HLA-matched cords (HLA-A,-B antigen; DRB1 potential allele) with higher cell doses as needed for hemoglobin disorders (TNC count of at least 5 × 10 7 cells/kg) could increase the alternative donor option. When this was examined, the probability of a potential 8/8 MUD, 5/6 or 6/6 unrelated cord in SCD improved the chances, but they remained relatively low at 45%.…”
Section: Alternative Donor Transplantationmentioning
confidence: 99%
“…When this was examined, the probability of a potential 8/8 MUD, 5/6 or 6/6 unrelated cord in SCD improved the chances, but they remained relatively low at 45%. 28 …”
Section: Alternative Donor Transplantationmentioning
confidence: 99%
“…However, this matching was done at the serological level for HLA-A and-Band at the potential allele level for -DRBl. A recentlook at this scenario that incorporated more detailed matching demonstrated that the chances of a sickle cell patient finding a potential allele 8/8 HLA-A,-B,-C and -DRBl MUD was only 19% [22]. Combining 5/6 and 6/6 HLA-matched cords (HLA-A,-B antigen; DRB1 potential allele) with higher cell doses as needed for hemoglobin disorder transplants (total nucleated cell count of at least 5 × 10 6 /kg) could increase the alternative donor option.…”
Section: Introductionmentioning
confidence: 99%